Enteropathy of coeliac disease in adults: increased number of enterochromaffin cells the duodenal mucosa. Issue 1 (January 1982) - Sjölund, K; Alumets, J; Berg, N O; Håkanson, R; Sundler, F
Abstract : Twenty-nine adult patients with coeliac disease and 39 patients with a normal duodenal morphology were studied with respect to the 5-ht containing enterochromaffin cells. Their number in duodenal biopsies was assessed by fluorescence histochemistry and they were examined by immunohistochemistry for peptides known or believed to occur in enterochromaffin cells. Antisera used were raised against substance P, motilin, and leu-enkephalin. In addition, the concentration of 5-HT was determined chemically. In adult coeliac disease there was a significant increase in the number of duodenal enterochromaffin cells compared with the control group. The concentration of 5-HT in the duodenal mucosa was also greatly increased. Substance P was found in a minority population of enterochromaffin cells. These cells were very few and did not increase in number in coeliac disease. Motilin cells were distinct from enterochromaffin cells. No enkephalin immunoreactive cells were found in the biopsies.